2019
DOI: 10.1038/s41389-019-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc transactivates GP73 and promotes metastasis of hepatocellular carcinoma cells through GP73-mediated MMP-7 trafficking in a mildly hypoxic microenvironment

Abstract: Golgi phosphoprotein 73 (GP73), encoded by GOLM1, is a highly expressed factor in hepatocellular carcinoma (HCC) cells and has been regarded for several years as a remarkable serum biomarker for the diagnosis of HCC. Recently, it was found that upregulation of GP73 promotes cancer metastasis, but the mechanism is complex, and it is even unclear how the gene is transactivated in HCC cells. In this study, it was discovered that c-Myc transactivated GP73 in a mildly hypoxic microenvironment and that the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
(30 reference statements)
0
31
0
Order By: Relevance
“…Among them, GOLM1 (also known as GP73 or GOLPH2) is the most anticipated tumor biomarker. A growing number of studies have shown that the abnormal expression of GOLM1 is associated with HCC and may become a new target for the prevention, monitoring and treatment of HCC [4][5][6][7]. In this review, we discuss the recent advances of GOLM1 in HCC and present an overall view of future research.…”
mentioning
confidence: 99%
“…Among them, GOLM1 (also known as GP73 or GOLPH2) is the most anticipated tumor biomarker. A growing number of studies have shown that the abnormal expression of GOLM1 is associated with HCC and may become a new target for the prevention, monitoring and treatment of HCC [4][5][6][7]. In this review, we discuss the recent advances of GOLM1 in HCC and present an overall view of future research.…”
mentioning
confidence: 99%
“…[ 40,43 ] Hypoxia can significantly reduce the effectiveness and cause resistance of radiotherapy and chemotherapy. [ 10 ] Possible reason is that hypoxia can increase expression of pre‐survival genes including c‐myc, [ 44 ] AMPK, [ 45 ] GLUT1, [ 46 ] and BNIP3. [ 47 ] Hypoxia can also promote tumor angiogenesis, [ 48 ] EMT, [ 49 ] invasion, [ 50 ] metastasis, [ 9 ] glycolysis, [ 51 ] metabolism, [ 52 ] and survival by regulate hundreds of genes involved in these processes.…”
Section: Resultsmentioning
confidence: 99%
“…Golgi phosphorylated protein 3 (GOLPH3) promotes the development of CRC and induce resistance to 5-FU by mediating the mTOR pathway [ 18 20 ]. Golgi membrane protein 1 (GOLM1) expression is correlated with early recurrence, metastasis, and poor survival of HCC patients [ 21 , 22 ]. Golgi vesicle transporter 1A (GOLT1A) has been shown to regulate tamoxifen sensitivity in breast cancer and promote cell proliferation in lung cancer [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%